Patterns of Adolescent Aggression and Victimization: Sex Differences and Correlates. Issue 9 (21st October 2019) - McNaughton Reyes, H. Luz; Foshee, Vangie A.; Chen, May S.; Ennett, Susan T.
ABSTRACT: This study identified heterogeneous patterns of peer and dating aggression and victimization among boys and girls and examined their relation to risk and protective correlates. Girls ( n  = 1648) and boys ( n  = 1420) in grades 8–10 completed surveys assessing 14 indicators of violence involvement. Latent class analyses indicated a four-class solution, though a test of measurement invariance indicated the nature of the classes differed by sex. Among boys and girls, three classes emerged: Uninvolved (45% of girls, 61% of boys), Peer Aggressor-Victims (23% of girls, 21% of boys), and Cross-Context Aggressor-Victims (CCAV) (12% of girls, 5% of boys). Those in the Peer Aggressor-Victims class were likely to report involvement in peer aggression only; however, girls in this class were likely to be involved only in moderate violence, whereas boys were likely to be involved in moderate and severe violence. Those in the CCAV class were likely to report involvement in all forms of violence except sexual and controlling aggression, which was likely only among boys. Among girls, but not boys, a Verbal Dating Aggressor-Victims class (21% of girls) emerged that was characterized by involvement in occasional verbal dating aggression only. Among boys, but not girls, a Cross-Context Physical Victims class (13% of boys) emerged that was characterized by being only a victim of moderate physical peer and dating violence. Unique and shared risk and protective factors distinguished class membership for girls and boys. Findings suggest the pathways leading to violence may differ by sex and result in different patterns of violence involvement.